Gaya Kelekatan Remaja dan Orang Tua pada Siswa SMP Negeri 1 Nguter Kabupaten Sukoharjo - Tedra, Latih Buran (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
Attachment theory adolescents and parents can be a shield for adolescents to avoid delinquency, so this study wanted to know what type of attachment that occurs between adolescents and parents. In line with the objectives of this study to describe the style attachment adolescents and parents in general, views on gender and parental education on students of SMP Negeri 1 Nguter Sukoharjo. The attachment scale given to 227 students and 9 respondents to be interviewed. Data were analysis using quantitative analysis includes a percentage descriptive and qualitative analysis of interviews. Found that the arising attachment style is a secure, refuse and preoccupied attachment style. Attachment theory is more secure and reject male dominated and preoccupied by women. Secure attachment is dominated by the college for dad and junior to the mother. Attachment theory rejects both dominated high school and attachment style preoccupied by father's education primary schools and colleges for the mother. Implications of the application of guidance and counseling, guidance and counseling teachers can collaborate with parents and teachers of other subjects to improve discussion and appreciation to students.